COMMUNICATION STRATEGIES EMPLOYED BY HEALTH PROFESSIONALS WITH HEARING IMPAIRED PEOPLE: AN INTEGRATIVE REVIEW - Vieira, Domisy de Araújo; Silva, Liliane Faria da; Machado, Maria Estela Diniz; Brandão, Euzeli da Silva; Chagas, Herleis Maria de Almeida (Cogitare Enfermagem, 2023)
Objective: to identify studies in the scientific literature on the communication between health professionals and hearing impaired people during care provision. Method: an integrative review carried out in February 2021 in 14 databases and with manual search, without time frame, in Portuguese, English, Spanish and through the Hearing Impaired People and Health Professionals descriptors and their variations, without context delimitation. The results were analyzed by organizing them into thematic groups according to their frequency. Results: a total of 16 studies were selected, with the following results standing out: use of writing and mimicry as main communication strategies; non-qualification of the professionals for effective communication, with the use of LIBRAS as the least used means; and feelings of insecurity, blockage and disability experienced by the professionals in communicating with hearing impaired people. Conclusion: it is necessary to invest in health professionals’ qualification in LIBRAS, making communication more effective and contributing to improvements in the care practice.